Factors affecting the mortality rates of filipino oral cancer patients at the Philippine General Hospital from 1984 to 1988 - Kawi, Heidi Frances; Vigilar, Maria Consuelo; Gervasio, Natividad (Adviser).
There is a need to gain more knowledge about the oral cancer scenario in the country since we are surviving to an age when the occurrence of degenerative diseases is higher. In addition, Philippine health statistics stress a need for an increased awareness of cancer and the extent to which it affects the sexes and the different age groups. Thus, the presence of cancer worldwide and its alarming state in the country challenges us to continue investigations into the relationships between cancer risks, lifestyles and inherent host factors. Bearing this in mind, we shall be able to gradually campaign towards prevention and an eventual decrease in mortality rates by means of improving diagnosis measures and health care services.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Mouth -- Cancer